(untitled) (Forest and Society, 2023)
The livelihoods of farmers in developing countries are often associated with the existence of forests, especially agroforestry. The dynamics of agroforestry and livelihoods could not be separated from the political context and developments in Indonesia. In this paper, the dynamics of Sustainable Livelihood Assets (SLA) owned by smallholder farmers are explored using three political sequences, namely the New Order Era, the Reform Era, and the Post-Reform Era. The result showed that the development of agroforestry in Gunungkidul had been primarily influenced by political initiatives that have a connection with vegetation coverage, livelihood assets, and species composition in the systems. The livelihoods possessed by farmers have been relatively sustainable during the past five decades; only a slight change could be observed in the ownership of capital. The political initiatives have been an enabling environment for agroforestry development that support sustainable livelihoods. The study recommends that the socio-political culture needs to consider the traditional agroforestry system in order to sustain the livelihoods of the people.